2010
DOI: 10.1111/j.1574-6941.2010.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoparasitism of arbuscular mycorrhizal fungi: a pathway for the entry of saprotrophic fungi into roots

Abstract: Within the rhizosphere, arbuscular mycorrhizal (AM) fungi interact with a cohort of microorganisms, among which is the biological control agent, Trichoderma spp. This fungus parasitizes a wide range of phytopathogenic fungi, a phenomenon also reported in the extraradical mycelium (ERM) of AM fungi. Here, we question whether the mycoparasitism of the ERM could be extended to the intraradical mycelium (IRM), thus representing a pathway for the entry of Trichoderma harzianum within the root. Microcosm experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 56 publications
0
28
2
Order By: Relevance
“…Other researchers also suggested that the effects of microbial community on AM fungi growth and function were greater than the reciprocal impact [60]. de Jaeger et al [61] demonstrated that Trichoderma harzianum was able to impact the viability of AM fungi by feeding on its intra- and extraradical mycelium under in vitro controlled conditions. In natural ecosystems, the rhizosphere effects may be the dominant influence [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers also suggested that the effects of microbial community on AM fungi growth and function were greater than the reciprocal impact [60]. de Jaeger et al [61] demonstrated that Trichoderma harzianum was able to impact the viability of AM fungi by feeding on its intra- and extraradical mycelium under in vitro controlled conditions. In natural ecosystems, the rhizosphere effects may be the dominant influence [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Penetration sites of the fungus into the root were recognized in our studies in the SEM (Figure 5(b)). De Jaeger et al (2010) [20] describe that Trichoderma harzianum is penetrating its host plant through the arbuscular mycorrhizal fungus Glomus. In our studies with mycorrhizal fungus staining the septate and coenocytic hyphae seem to grow next to each other outside and inside the root (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…2009). Interestingly, De Jaeger et al. (2010a) also reported mycoparasitism of Trichoderma harzianum over AM fungi.…”
Section: Introductionmentioning
confidence: 99%